Impact of maternal iron deficiency on the auditory functions in the young and adult guinea pig. (3rd June 2019) - Shero, Nora; Fiset, Sylvain; Blakley, Brian; Jougleux, Jean-Luc; Surette, Marc E.; Thabet, Mohamed; Rioux, France M.
Abstract : Objectives: The aim of this study was to evaluate the hearing function in the guinea pig offspring at post-natal day (PNd) 24 and PNd84 born from dams suffering from iron deficiency during pregnancy and lactation by using the auditory brainstem response (ABR). Method: Female guinea pigs ( n  = 24 per dietary group) were fed an iron sufficient (IS) diet (114 mg/kg) or an iron deficient (ID) diet (11.7 mg/kg) during the gestation and lactation periods. Pups in both groups were weaned at PNd9 and given the IS diet. The hematocrit level was measured at every trimester of pregnancy and at the day of sacrifice in dams and at PNd24 and PNd84 in pups. The animal body weight was measured on every second day until the day of sacrifice. The ABR was used in pups to measure the hearing threshold using a broad range of stimulus intensities and latency at 100 and 80 dB in response to 2, 4, 8, 16, and 32 kHz tone pips at PNd24 and 84. Results and discussion: No significant difference between dietary groups was measured in hearing threshold and absolute latencies in pups at PNd24 and PNd84. Although the ID offspring ( n  = 16) did not differ in brainstem transmission times (BTTs) at 80 dB compare to the IS siblings ( n  = 25) at PNd24, they showed significant delayed inter-peak latency (IPL) I-IV at 100 dB suggesting a delayed BTT. At PNd84, the latency of all peaks including IPL I-IV at 80 and 100 dB significantly decreased and was also similar in pups from both dietary groups suggesting a better brain maturation. This is the first study investigating the long-term impact of maternal iron deficiency on the auditory functions in the guinea pig offspring during early development to adulthood.